Evaluation of simulator tools and power‐aware scheduling model for wireless sensor networks. Issue 5 (9th August 2017) - Chéour, Rym; Jmal, Mohamed Wassim; Kanoun, Olfa; Abid, Mohamed
Abstract : The sharp increase of the wireless sensor networks (WSNs) performance has increased their power requirements. However, with a limited battery lifetime it is more and more difficult to deploy many more sensors with today's solutions. Therefore, the authors need to implement autonomous WSNs without any human intervention or external power supply. To this end, this study proposes an effective strategy to ensure an energy consumption gain that takes into account time constraints through a power‐aware model based on the dynamic voltage and frequency scaling and the dynamic power management that are appropriate to the WSNs and on a global Earliest Deadline First scheduler. To select the most suitable simulator to integrate and simulate the developed models, >25 of the existing WSN simulators are outlined and evaluated. On the basis of this comparative study analysis, the authors chose the simulation tool for real‐time multiprocessor scheduling (STORM) to validate their work for its multiple advantages.